Evaluation of Oral Amoxicillin/Clavulanate for Urinary Tract Infections Caused by Ceftriaxone Non-Susceptible Enterobacterales - Madison E. Salam; Meghan Jeffres; Kyle C. Molina; Matthew A. Miller; Misha Huang; Douglas N. Fish (MDPI AG, 2024)
Urinary tract infections (UTIs) are one of the most common infections and are frequently caused by Gram-negative organisms. The rise of resistant isolates has prompted evaluation of alternative therapies, including amoxicillin-clavulanate which has potent activity against Ambler class A enzymes. This study sought to evaluate clinical outcomes of patients with ceftriaxone non-susceptible UTIs receiving amoxicillin-clavulanate or standard of care (SOC). This was a single-center, retrospective, cohort study of adult patients with urinary tract infections caused by a ceftriaxone non-susceptible pathogen who received amoxicillin-clavulanate or SOC. The primary outcome was clinical failure at 90 days. Secondary outcomes included time to failure, isolation of a resistant organism, and hospital length of stay. Fifty-nine patients met study inclusion: 26 received amoxicillin/clavulanate and 33 received SOC. Amoxicillin-clavulanate recipients did not have higher failure rates compared to SOC recipients. For patients requiring hospital admission, hospital length of stay was numerically shorter with amoxicillin-clavulanate. The frequency of amoxicillin-clavulanate and carbapenem-resistant organisms did not differ significantly between groups. Amoxicillin-clavulanate may be a useful alternative therapy for the treatment of ceftriaxone non-susceptible Enterobacterales UTIs.